Molecular and thermal characterization of starches isolated from African rice (Oryza glaberrima). (7th September 2015) - Gayin, Joseph; Bertoft, Eric; Manful, John; Yada, Rickey Y.; Abdel‐Aal, El‐Sayed M.
Abstract : Starch is the principal component of rice that affects its cooking and nutritional quality. This study investigated molecular and thermal properties of starches isolated from seven Africa rice accessions (ARAs) in comparison with two commonly produced Asian rice varieties (ARVs) and a developed cross ( sativa × glaberrima ) variety (NERICA 4). All starch granules were polyhedral and tightly packed with size distribution ranging from 2–22 µm and displayed type‐A X‐ray diffraction pattern. ARAs starch granules had higher ratio of absorbance to scattering when exposed to iodine vapor exhibiting greater flexibility and availability of glucan chains to form complexes with iodine as compared to ARVs. The enthalpies of starch gelatinization (15.1–15.8 J/g) and retrograded gel melting (9.2–10.8 J/g) were higher in ARAs than in NERICA 4 (14.5 and 9.2 J/g, respectively) and ARVs, (13.3–14.3 and 6.4–7.3 J/g, respectively) possibly due to their higher amylose content and longer chains. Significant ( p  < 0.05) differences in peak, trough, final, breakdown, and setback viscosities were also observed among the starches with Koshihikari Asian rice having the highest peak viscosity (310 RVU). These differences in molecular structure and thermal properties between the ARAs and ARVs are likely to influence the cooking and eating quality of the ARAs.